La chaine hercynienne au Pérou et en Bolivie; premiers résultats - Mégard, Francois (1971)
The main part of the basement of the Peruvian and Bolivian Andes is formed by the remnants of a Hercynian intracratonic range in which some elements of the Precambrian basement are reworked. The Hercynian sedimentary prism is made of thick detrital Lower Paleozoic sediments, which are partly flysch-like but seem to be never associated with ophiolites. Those sediments were strongly disturbed by the Upper Devonian « Eohercynian » folding ; they display close folds with axial-plane cleavage which result of at least two subphases of deformation, in some areas a greenschist facies metamorphism is associated with the folds. On the whole the range does not show any preferential vergence. The Eohercynian folded complex and its unconformable caver of Carboniferous and Lower and Middle Permian sediments are reworked at the end of the Middle Permian by the Late Hercynian movements which in Peru are in most cases only epirogenetic. The magmatism is mostly post-tectonic, granitic rocks are intruded and andesitic tu rhyolitic breccias and slows are interstratified in the Carboniferous and Upper Permian molasses. The chronology of the Hercynian deformation is difficult to establish in Bolivia because i) of the lack of a Permo-Garboniferous caver in the intensely folded axial part of the chain and ii) of the quite complete hiatus of the Upper Permian, Trias and Jurassic. This chronology is infered from the study of the less deformed adjoining regions where the Permo-Carboniferous is present and from considerations about the style and direction of the structures. The result is that in Bolivia the main folding is due to the Late-Hercynian phase. The Peru-Bolivia Hercynian range runs over more than 2 500 km and is connected « en échelon » to the Chile-Argentina Hercynian branch wellknown in the Frontal Cordillera and the Precordillera of Argentina. This branch is a part of the great Hercynian « Samfrau orogene )) which was bordering the Gondwana before ist breaking up and the other elements of which are found in South Africa, in Antarctide and in Australia.